(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Because adolescent substance abuse is common, and research have shown that drugs usage is primarily linked to the taking of cigarettes and alcohol, an early extensive study of substances misuse generality, that includes cigarettes and alcohol consumption, would seem to be the fundamental factor in avoiding and taking control of drug consumption. The purpose of this research was to look at articles published in Iran over the previous decade that looked at those researches on the use of drugs by the students of high school. From 2001 to 2011, publications regarding student drug use were obtained from national databases, with seven papers on 14–19 year old high school students being analyzed. Cigarettes and hookah were the most often used substances, and then alcohol, hash, opium, ecstasy, and heroin, according to the seven publications analyzed. Opium and heroin use was four to five times greater in Kerman than in other cities studied. The use of drugs is quite common among the society’s teenagers and young people therefore, they need proper attention and elicit and decisive response.